2014
DOI: 10.4209/aaqr.2014.01.0005
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment and Characterization of Particulate Matter (PM10) in Urban Environment of Lahore

Abstract: The present study describes the characterization of carbonaceous species including elemental carbon (EC), organic carbon (OC), total carbon (TC), crustal (Al, Ca, Mg, Fe, S, and Ti) and trace metals (As, Ba, Cd, Cr, Cu, Mn, Ni, Pb, Sn and Zn) in PM 10 samples collected from an urban site in Lahore, Pakistan. Sources of various pollutants and their characterization positive matrix factorization (PMF) model. The carbonaceous species (TC, OC, EC) and metals were measured in PM 10 samples by NIOSH protocol using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 77 publications
2
53
1
Order By: Relevance
“…Similarly, respirable PM 10 annual average concentration of 336 µg m -3 were reported by Stone et al (2010). Likewise Alam et al (2014) reported that PM 10 concentration at an urban site in Lahore varied from 254 µg m -3 to 555 µg m -3 with an average of 406 µg m -3 . In Faisalabad city average PM 10 concentrations of 372 µg m -3 , 283 µg m -3 , 223 µg m -3 and 150 µg m -3 were observed at designated sites by Zafar et al (2015).…”
Section: Particulate Mattermentioning
confidence: 89%
“…Similarly, respirable PM 10 annual average concentration of 336 µg m -3 were reported by Stone et al (2010). Likewise Alam et al (2014) reported that PM 10 concentration at an urban site in Lahore varied from 254 µg m -3 to 555 µg m -3 with an average of 406 µg m -3 . In Faisalabad city average PM 10 concentrations of 372 µg m -3 , 283 µg m -3 , 223 µg m -3 and 150 µg m -3 were observed at designated sites by Zafar et al (2015).…”
Section: Particulate Mattermentioning
confidence: 89%
“…Tian et al (2013) reported that the PM 10 OC and EC concentrations in the ambient air of Taiyuan, Shanxi, were 25.89 and 6.82 µg/m 3 in summer, respectively. The corresponding values in Lahore, Pakistan were 63 and 21 µg/m 3 (Alam et al, 2014). Samara et al (2014) reported values of 11.3 and 6.56 µg/m 3 at an urban traffic site in Thessaloniki, northern Greece.…”
Section: Characteristics Of Oc and Ecmentioning
confidence: 99%
“…Elemental carbon and organic carbon [87] From Black carbon [111] From an urban center of Lahore during a high polluting spring episode with sampling duration from March to April of 2006 Hopanes, benzo[ghi]perylene, coronene, and picene [112] From a high-traffic site in Lahore having adjoining airport area with sample collection at 5 min intervals from November 2005 to January 2006…”
Section: Sources Of Elemental Emissionsmentioning
confidence: 99%
“…Al, Ca, Cd, Cr, Cu, Fe, Mg, Mn, Ni, Pb, and Zn [87] From indoor and outdoor environment of various industrial and residential sites located in the metropolitan city of Lahore during December 2001 to January 2002 with sampling duration of 8-24 h Cu, Zn, Cd, and Pb [47] In total, 402 samples were collected from an urban site of Karachi during January 2006 to January 2008 (three times per week) with sampling duration of 24 h Cd, Ba, K, Zn, Ni, As, Pb, Na, and Cr [93] In total, 84 samples were collected from commercial and residential areas of Rawalpindi and Islamabad for continuous sampling of 7 months with frequency of one sample per week Cd, Pb, Zn, Ba, Co, Fe, Cr, and Ce [54] From Karachi (urban site), Lahore (residential site), Rawalpindi (densely populated commercial site), and Peshawar (road site) during March and April of 2010…”
Section: Sampling Detail Major Species Analyzed Referencementioning
confidence: 99%
See 1 more Smart Citation